Development of analytical probabilistic model parameters for urban stormwater management - Salisu Dan’Azumi,; Supiah Shamsudin,; Azmi Aris, (Universiti Kebangsaan Malaysia, 2013)
Analytical probabilistic models (APM) are closed form mathematical expressions for long term system’s output performance derived from the probability distribution of the system’s input variables. In order to apply the APM for urban stormwater control systems’ design, APM parameters have to be made known. These input parameters include APM parameters which are derived from the meteorological rainfall characteristics; storm depth, duration, intensity and inter-event time. This study is aimed to develop meteorological APM parameters that can be used for detention pond design in Peninsular Malaysia. Hourly rainfall data covering 10 to 40 years period were analyzed from 13 different locations spread across the Peninsular. The data were analyzed to obtain the APM parameters at different values of minimum storm separation time (MSST). The APM parameter of rainfall duration (λ) was found to range from a mean value of 0.260 h-1 for 2 h MSST to 0.04 h-1 for 24 h MSST. The APM parameter of rainfall volume (ζ) ranges from a mean value of 0.091 mm-1 for 2 h MSST to 0.038 mm-1 for 24 h MSST. Similarly, the APM parameter of rainfall intensity (β) ranges from a mean value of 0.355 h/mm for 2 h MSST to 0.504 h/mm for 24 h MSST. Finally, the APM parameter of inter-event time (ψ) ranges from a mean value of 0.025 h-1 for 2 h MSST to 0.012 h-1 for 24 h MSST. Once the APM parameters are determined for a particular area, the long term stormwater control systems’ performance can easily be determined.